2002
DOI: 10.1021/jo026466c
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Aryl Radicals from Arylboronic Acids by Manganese(III) Acetate:  Synthesis of Biaryls and Heterobiaryls

Abstract: The efficient generation of aryl radicals from arylboronic acids by manganese(III) acetate is described. In aromatic solvents, in situ generated aryl radicals afford the corresponding biaryls in very good yields. This method works selectively, and yields are better than those from similar, previously described methods. Arylboronic acids carrying sensitive functional groups also work efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…[16] Other recently developed methods for the generation of aryl radicals include the irradition of iodonium salts [17] and the treatment of arylboronic acids with the strong oxidant manganeseA C H T U N G T R E N N U N G (III) acetate. [18] Among all the reaction principles mentioned, ar-A C H T U N G T R E N N U N G enediazonium salts probably offer the most convenient and cost-effective access to aryl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Other recently developed methods for the generation of aryl radicals include the irradition of iodonium salts [17] and the treatment of arylboronic acids with the strong oxidant manganeseA C H T U N G T R E N N U N G (III) acetate. [18] Among all the reaction principles mentioned, ar-A C H T U N G T R E N N U N G enediazonium salts probably offer the most convenient and cost-effective access to aryl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Shortened times afforded disappointing results (Entry 12). Use of a higher loading of iodine was favorable for the synthesis of biphenyl (Entries [13][14], whereas with TBAB (nBu 4 NBr) or LiCl as the additive we were unable to achieve enhanced results (Entries [15][16]. Use of more iodine or of a longer reaction time (48 h) afforded better yields (Entries [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Actually, it has been reported that aryl radicals are generated from aryl-boronic acids in the presence of some oxidants. [13,18] In addition, Demir et al observed that aryl radicals were obtained from arylhydrazines in the presence of the potassium permanganate/carboxylic acid/organic solvent system. [19] Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arylboronic acid has been employed as an aryl source in the synthesis of 2-arylfuran under Mn(II) acetate-promoted radical reaction conditions. Although the yields are not high, they are better than those of the phase-transfer Gomberg-Bachmann synthesis using arenediazonium ions [59]. Arylation of 3-furoate with 3-bromonitrobenzene using Pd(PPh 3 ) 4 as catalyst in toluene affords 2,3-disubstituted furan while 5-aryl products are generated predominantly when Pd/C is used as the catalyst and NMP as solvent [60].…”
Section: Monosubstituted Furansmentioning
confidence: 94%